The Impact of New Media Platforms Towards Social Shaping and Culture Interaction Among Universiti Sains Islam Malaysia Students - Nurun Anis Nabila DarulIkhsan; Norsimaa Mustaffa (USIM Press, 2024)
AL-I’LAM–J.Contemp.Islam.Comm.&Media Vol.3,Issue1